Computer-Assisted Language Learning (CALL) in Medical Education - Abrahamyan, A.; Hayrapetyan, A. A.; Nalbandyan, S. R.
This article, " Computer-Assisted Language Learning (CALL) in Medical Education," honors the memory of Professor Mikhail Davidovich Amirkhanyan and examines the transformative role of CALL in modern medical education. It presents CALL as more than a teaching aid—rather, a dynamic and adaptive approach that integrates digital tools, artificial intelligence, and multimedia to foster professional fluency in foreign languages. Focusing on tailored strategies such as specialized vocabulary modules, real-time communication practice, and mobile learning applications, the study highlights how CALL enhances both linguistic competence and cultural sensitivity. It also addresses key challenges in implementation and offers practical solutions to support its integration into medical curricula. The article concludes that CALL is not merely a pedagogical innovation but a necessary instrument in preparing globally competent healthcare professionals for the demands of contemporary clinical practice. Սույն հոդվածը՝ «Օտար լեզվի ուսուցման համակարգչային տեխնոլոգիաները (CALL) բժշկական կրթական համակարգում» նվիրված է պրոֆեսոր Միխայիլ Դավթի Ամիրխանյանի հիշատակին: Ներկայացվում է CALL-ի դերը որպես նորարարական կրթական մոտեցում՝ ուղղված օտար լեզվի արդյունավետ տիրապետմանը մասնագիտական միջավայրում։ CALL-ը դիտարկվում է ոչ թե որպես սովորական ուսուցողական գործիք, այլ՝ որպես ինտեգրացված, տեխնոլոգիապես հագեցած մեթոդաբանական համակարգ, որն ապահովում է բազմաչափ ուսուցում՝ համադրելով թվային հարթակներ, արհեստական բանականություն և բազմամեդիա լուծումներ։ Настоящая статья «Обучение иностранному языку с использованием компьютерных технологий (CALL) в системе медицинского образования» посвящёна памяти профессора Михаила Давидовича Амирханяна. Раскрывается значение CALL как инновационного подхода к обучению, направленного на эффективное овладение иностранным языком в профессиональной среде. CALL рассматривается не как обычный учебный инструмент, а как интегрированная, технологически оснащённая методологическая система, обеспечивающая многомерное обучение посредством цифровых платформ, искусственного интеллекта и мультимедийных решений.
Keywords: Methodology